Community, Court, and Conciliation: Designing a Hybrid Mediation Model for Islamic Divorce Adjudication - Solihin, Rohmad Agus; Fauzi, Imron (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2025)
The appointment of a hakam, an individual who mediates disputes, in divorce proceedings constitutes a crucial mechanism for advancing justice and reconciliation within both Islamic law and the Indonesian judicial system. This study offers a comparative analysis of two predominant hakam models in Jember Regency: the formal-institutional approach utilized by the Religious Court and the communal-cultural approach practiced by community leaders or local religious figures (Kiai). Employing a qualitative case study methodology, the research draws on data collected through in-depth interviews with ten purposively selected participants, including judges, mediators, religious leaders, community elders, and divorced individuals, supplemented by direct observation and document analysis. The findings reveal that the formal-institutional model ensures legal certainty through standardized mediation procedures; however, it often overlooks the social and cultural dimensions of marital conflict. Conversely, the communal-cultural model emphasizes empathy, religious authority, and contextual harmony but lacks binding legal authority and enforceability. This study underscores the potential for synergy between formal legal mechanisms and socio-cultural practices. It contributes to the literature by proposing a hybrid hakam framework that integrates procedural justice with cultural responsiveness, demonstrating how the convergence of legal formalism and communal concern can enhance the effectiveness, fairness, and cultural relevance of Islamic divorce resolution in Indonesia.